Integrated Evaluation of Multi-Solvent Extracts from Selected Medicinal Plants: In Vitro and In Vivo Assessment of Biological Activities - KERROUCHE Halima; BOUGHEZALA Meriem; BEN AMOR Saad Eddine (جامعة الوادي .University of EL-OUED., 2025)
Diabetes mellitus is a group of metabolic disorders characterized by chronically elevated blood glucose levels due to impaired insulin secretion, insulin action, or both. This condition is often associated with serious complications, and current synthetic treatments may have limited effectiveness or undesirable side effects. For this reason, the World Health Organization (WHO) has recommended the use of traditional medicine as an alternative or complementary approach to modern therapies. This study aims to evaluate the antidiabetic and anti-inflammatory effects of Ammodaucus leucotrichus and Mentha piperita extracts through both in vivo and in vitro experiments. It also includes the analysis of active chemical compounds using LC-MS technology, with the goal of exploring their potential as natural alternatives for managing diabetes and its inflammatory complications. Experimental diabetes was induced in rats by intraperitoneal injection of a freshly prepared solution of alloxan, a compound known to destroy pancreatic β-cells and trigger multiple inflammatory responses. The rats then underwent a 7-day treatment protocol, during which fasting blood glucose levels and body weight changes were monitored to assess treatment efficacy. The study included eight groups: a healthy untreated control group, an untreated diabetic group, a diabetic group treated with an antidiabetic drug, a diabetic group treated with Ammodaucus leucotrichus extract, a diabetic group treated with Mentha piperita extract, and a diabetic group treated with an antiinflammatory drug. The results showed that diabetic rats treated with the plant extracts experienced significant reductions in blood glucose levels and inflammation markers, indicating dual antidiabetic and antiinflammatory activity. Additionally, the chemical composition of the extracts was analyzed using liquid chromatography–mass spectrometry (LC-MS) to identify the active compounds responsible for these effects. To assess in vitro antidiabetic activity, an α-amylase inhibition assay was conducted using both extracts. Results revealed that both A. leucotrichus and M. piperita inhibited the enzyme in a dose-dependent manner, with IC₅₀ values of 2.434 and 3.684 µg/mL respectively. The maximum inhibition rate reached 85.36 ± 0.12%, indicating strong potential to slow starch digestion and reduce glucose absorption.
Applied Biochemistry
Keywords: Mentha piperita; Ammodaucus leucotrichus; diabetes mellitus; alloxan; α-amylase; rats; inflammation; LC-MS..